Meta-Analisis: The Impact of Smoking Habits and Hypertension on Coronary Heart Disease in Productive Age Group - Pagan, Putri Nurul Aqla; Kalsum, Ummi; Guspianto, Guspianto; Fitri, Adelina; Halim, Rd. (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
The global disease burden has shifted epidemiologically toward non-communicable diseases (NCDs), with coronary heart disease (CHD) as the leading cause of global mortality, contributing to 36% of deaths. Objective: This study aimed to identify the effect size and variability model of CHD determinants in the productive age group. A systematic review and meta-analysis approach was conducted between January and May 2025. Primary data were retrieved from Google Scholar, PubMed, and Scopus, restricted to studies published from 2019 to 2023. Out of 18,132 articles identified, 12 studies met the eligibility criteria. Data were analyzed using STATA 17.0. The systematic review protocol was prospectively registered in PROSPERO (Registration: CRD420250602556). The proportion of CHD in the productive age group was 5.3% (95% CI: 1.50–9.00). The meta-analysis of smoking habits showed a non-significant association with CHD (OR = 1.29; 95% CI = 0.54–1.69; p = 0.397), whereas hypertension was found to have a significant impact (OR = 1.95; 95% CI = 1.49–2.42; p = 0.176). No publication bias was detected. Hypertension significantly contributes to the incidence of CHD in the productive age group. CHD prevention should target this age group, especially in countries with high CHD prevalence. Interventions should include physical activity promotion, aggressive anti-smoking campaigns, nutritional education to reduce obesity, and early screening and management of diabetes and hypertension at the primary healthcare level.